2017
DOI: 10.1080/14681811.2017.1362633
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment through sex education? Rethinking paradoxical policies

Abstract: Youth empowerment is the main goal of sex education according to Dutch Government and NGO policies. Academics from different disciplines have argued, however, that the ideal of empowerment through education is problematic, because of the unequal power relations implicated in educational practices. Building on one-anda-half years of online and offline ethnographic fieldwork among Dutch youth, this article argues that Dutch sex educational policies inhibit rather than encourage young people's empowerment by allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…Instead, the emphasis is on a collaborative approach between adults and young people, in which they come together to rethink social issues and develop solutions. Naezer et al (2017) suggest that "sexual knowledge building" should replace "sex education" (p. 713). They conceptualise the former as less formal, didactic, and moralising than the latter, and more of a process focused on information, understanding, and contexts of learning.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the emphasis is on a collaborative approach between adults and young people, in which they come together to rethink social issues and develop solutions. Naezer et al (2017) suggest that "sexual knowledge building" should replace "sex education" (p. 713). They conceptualise the former as less formal, didactic, and moralising than the latter, and more of a process focused on information, understanding, and contexts of learning.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Botswana, Nigeria and South Africa have shown that sexuality education may contribute to overcoming the adolescents SRH challenges that Zambia and other countries face [1517]. At the core of the Zambian sexuality education policy is the idea that there is a substantial need to support adolescents in delaying their sexual debut, to reduce the number of sexual partners and to increase safer sexual practices [1517].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Botswana, Nigeria and South Africa have shown that sexuality education may contribute to overcoming the adolescents SRH challenges that Zambia and other countries face [1517]. At the core of the Zambian sexuality education policy is the idea that there is a substantial need to support adolescents in delaying their sexual debut, to reduce the number of sexual partners and to increase safer sexual practices [1517]. Backed by evidence on its positive effects on adolescents’ level of knowledge, skills, attitudes and values related to sex and sexuality, CSE has been promoted in a series of global policy guidelines and recommended to be integrated into ordinary school curricula [3, 1517].…”
Section: Introductionmentioning
confidence: 99%
“…The tension between, on the one hand, a sex education that takes a stand for certain values and, on the other, tactics that strive to open up and involve students in a critical pedagogy, is not easily resolved and perhaps should not be resolved. However, we believe it is crucial to acknowledge these tensions and invite students to explore what we need to think and 'do differently' (Youdell 2011, 12, but see also Naezer, Rommes, and Jansen 2017;Sanjakdar et al 2015) in order to challenge social and sexual injustice, both within and outside school.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars argue for the need for an empowering critical pedagogy, where students are the subjects rather than the objects subjected to adult regimes of sex education (Naezer, Rommes, and Jansen 2017). Scholars such as Sanjakdar et al (2015) emphasise that in order to implement such ideals, attention to the hegemony of teaching practices in this area, including aspects of authority and subordination, is central.…”
Section: The Current Call For Inclusion and Equality In Sex Educationmentioning
confidence: 99%